2021
DOI: 10.1111/ijfs.15413
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining of Chickpea Protein Isolate and its Application as Coating Enriched with Essential Oils from Satureja Hortensis and Satureja Mutica in Egg at Room Temperature

Abstract: Eggs are one of the most nutritious products on a daily basis. The objective of present research is to investigate the impact of coatings on improving storage time and internal quality of eggs. Coating treatments included control (C), coated with chickpea protein isolate (CPI), coated with PI containing Satureja hortensis (CPISH), coated with PI containing Satureja mutica (CPISM). Internal quality was assessed by air cell depth, shell strength, weight loss, haugh unit, yolk and albumen pH, yolk index, microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Therefore, the YI-based yolk quality was expected to be better for eggs coated with GBF/TAH, as it contributed to smaller changes in albumen quality, as supported by the higher HU. Farnejad et al [ 38 ] showed that Satureja hortensis and Satureja mutica essential oils added to chickpea protein isolate coating positively influenced the yolk quality of eggs stored for 7 weeks at 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the YI-based yolk quality was expected to be better for eggs coated with GBF/TAH, as it contributed to smaller changes in albumen quality, as supported by the higher HU. Farnejad et al [ 38 ] showed that Satureja hortensis and Satureja mutica essential oils added to chickpea protein isolate coating positively influenced the yolk quality of eggs stored for 7 weeks at 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the coatings may have preserved more of the ovomucin, as this is a protein that plays an important role in maintaining the viscosity and height of the same [29]. Protein coatings with essential oils can be efficient tools to keep the HU within the ideal range for grading the quality of eggs (AA) stored at room temperature [22,30].…”
Section: Resultsmentioning
confidence: 99%
“…Microstructure of yogurts was investigated using SEM (JSMe6390 LV, Japan) at 20 kV expediting voltage, and treatments were lyophilised through a freeze dryer. Small treatments of dehydrated yogurt were set on aluminium SEM stub with adhesive carbon fibre and coated with a thinner gold film (Farnejad et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%